2018
DOI: 10.1055/a-0746-4014
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Levels in Basal Conditions and During Glucose Tolerance Test in Prediabetic and Diabetic Patients

Abstract: Ghrelin is associated with glucose homeostasis but its’ possible relevance with glucose levels in physiological and pathological conditions has so far been poorly investigated. The aim of the present study was to evaluate circulating ghrelin levels in prediabetic and diabetic patients in basal conditions and in response to oral glucose tolerance test (OGTT). A total of 90 male adults aged 40 – 73 years old were enrolled in our study. Fasting and postprandial plasma ghrelin, insulin and glucose levels were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
4
0
2
Order By: Relevance
“…Ghrelin responses did not differ between the two groups. This confirms earlier findings that the levels are similar in subjects with or without impaired glucose tolerance [22] and with or without obesity [9]. Levels of glucagon are generally elevated in patients with insulin resistance and type 2 diabetes [5,14,16,23].…”
Section: Hormonal Changessupporting
confidence: 90%
“…Ghrelin responses did not differ between the two groups. This confirms earlier findings that the levels are similar in subjects with or without impaired glucose tolerance [22] and with or without obesity [9]. Levels of glucagon are generally elevated in patients with insulin resistance and type 2 diabetes [5,14,16,23].…”
Section: Hormonal Changessupporting
confidence: 90%
“…On the other side the ghrelin peptide, as encoded by the same preproghrelin gene which produce the opposite peptide obestatin, it seems to play a crucial role in glucose and insulin metabolism and in development of obesity and DMT2. In our previous work [44], which included a partially overlapped population we observed that both peptides in fasting condition appear with lower levels in subjects with diabetes compare to controls, but not in prediabetics. In terms of comparison with other variables such as glucose, insulin and triglycerides in subjects with diabetes in both peptides we observed that they were inversely correlated with each peptide, concluding that ghrelin and obestatin behave differently in people with diabetes.…”
Section: Discussionmentioning
confidence: 64%
“…In clinical studies, fasting ghrelin concentration was low in obese individuals, and ghrelin concentrations decreased after nutrient loading . While exogenous ghrelin administration in humans was shown to inhibit β and worsen glucose tolerance, few studies have reported the relationship between ghrelin secretion and β during the OGTT …”
Section: Introductionmentioning
confidence: 99%
“…18 While exogenous ghrelin administration in humans was shown to inhibit β and worsen glucose tolerance, 19,20 few studies have reported the relationship between ghrelin secretion and β during the OGTT. 21 The present study tested the hypothesis that, in the OGTT, ghrelin dynamics are associated with β. The relationship between SI and β was first analyzed in young subjects with NGT, and indicators to determine DI were obtained.…”
Section: Introductionmentioning
confidence: 99%